STUDI PERSEPSI PELANGGAN DALAM PENINGKATAN KEPUASAN WISATA PADA MUSEUM KARS INDONESIA - Anggraini, Fusca Asti; Wiyono, Gendro (Prodi Magister Manajemen FE-UST, 2017)
This study discussess customers perception to increase tourism satisfaction in the Kars Museum Indonesia. The population are all traveller in the area of museum with 100 people as sample. The collecting data used questionare structurally and scale likert. The analyse data used Structural Equation Modeling (SEM) with Patial Least Square (PLS). Based on path analyse can be concluded that direct effect on tourism attractions toward satisfaction tourist is the best perception with a total effect of 0.425, tourist guide towards satisfaction tourist is the worst perception with a total effect of 0.291 so that it need improvement and enhancement. The result of study showed that variables educational content, tourism attractions and tourist guides have a significant effect on the perception of visitors and simultaneously affect sigificant to visitors perception with a coefficient of 0.641. Keywords: Attraction, Educational Contents, Perception, Satisfaction, Tourist Guide